Asymmetrical competition between aquatic primary producers in a warmer and browner world - Vasconcelos, Francisco Rivera (2016)
In shallow lakes, pelagic and benthic producers engage in spatially asymmetrical resource competition. Pelagic producers intercept the flux of light to the benthic habitat and benthic producers intercept the flux of sediment-derived nutrients to the pelagic habitat. In boreal and subarctic regions, climate change is affecting this interaction both directly through warming and indirectly through increased loading with colored dissolved organic matter (cDOM) from the catchment ("brownifcation"). We use a dynamical ecosystem model to explore the consequences of these changing environmental conditions for lake primary production and compare model predictions with the results of an experiment in which we manipulated water temperature and cDOM supply in a 2 × 2 factorial design. The experiment was performed in feld mesocosms large enough to harbor reproducing fsh populations and was run over an entire growing season. In agreement with model predictions, benthic algal production and biomass declined and pelagic algal production and biomass increased with browning. Pelagic nutrient concentrations diverged over time between low and high cDOM treatments, suggesting that browning alleviated pelagic algal nutrient limitation by shading benthic competitors and preventing them from intercepting the release of nutrients from the sediment. Warming considerably reduced benthic and pelagic algal production as well as pelagic algal biomass and total phosphorus. The warming results are only in partial accordance with model expectations, but can be explained by an indirectly inferred, positive response of macrophyte production (which was not included in the model) to warming. Our study suggests that lake ecosystem responses to climate change are mediated by cross-habitat feedbacks between benthic and pelagic producers.